Dostoyevsky's First Bibliographer. (2nd April 2016) - Andrianova, Irina
ABSTRACT: The article is devoted to the bibliographical work carried out by Anna Dostoevskaia, wife of novelist Fyodor Dostoyevsky. She became the first bibliographer of his literary work by compiling and publishing Bibliograficheskii ukazatel' sochinenii F. M. Dostoevskogo [Bibliographical index of the works of F. M. Dostoyevsky] in 1906. The article draws from Dostoevskaia's memoirs and archival resources, exploring the history of the bibliographical index, the textual challenges in the process of its compilation, and its enduring importance in Dostoyevsky studies. Dostoevskaia persevered until the end of her life (1918) to compile a second part to the index, but it remains unfinished. In 1929 the Dostoyevsky Memorial Museum was restructured and its collections scattered to various libraries and archives in Russia and beyond. Today researchers are working to restore a digital version of Dostoevkaia's Bibliographical Index and to reconstruct the Dostoyevsky Memorial Museum virtually.